Transfer of Irrigation Management Services. Guidelines - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
DL Vermillion and JA Sagardoy.FAO Irrigation & Drainage PaperNo. 58. 1999. 98 pp.ISBN 92 5 104308 6.US$14 Euro 14See earlier FAO reference for address.